2012
DOI: 10.4103/1450-1147.103413
|View full text |Cite
|
Sign up to set email alerts
|

18 F-FLT-PET for response evaluation of MEK inhibitor selumetinib (AZD6244, ARRY-142886) in patients with solid tumors

Abstract: Selumetinib (AZD6244, ARRY-142886) is a potent, selective, uncompetitive inhibitor of MEK 1 / 2, part of the RAF/MEK/ERK protein kinase signal cascade, which is responsible for tumor. This pilot study was used to explore if 18F-fluoro-l-thymidine (FLT), a thymidine analogue positron emission tomography (PET) tracer and a surrogate marker for proliferation, can be used as an early predictor of response for patients with solid cancers treated with Selumetinib. FLT-PET scans were performed in four patients at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, to date, the potential of FLT-PET for the early response evaluation of CRC during chemotherapy has been investigated in only three clinical studies with 2, 12 and 18 patients, respectively [1719]. Just one of these studies used liver metastases as measurable outcome lesions [17], while none of them used the currently preferred treatment regimen, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, to date, the potential of FLT-PET for the early response evaluation of CRC during chemotherapy has been investigated in only three clinical studies with 2, 12 and 18 patients, respectively [1719]. Just one of these studies used liver metastases as measurable outcome lesions [17], while none of them used the currently preferred treatment regimen, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…98 18 F-FLT PET has not yet been utilized in a trial of a PI3K pathway inhibitor; however, it has been incorporated into a clinical trial of the MEK inhibitor AZD6244 (selumetinib) as a single agent. 105 In this pilot study, 18 F-FLT PET scans were performed in four patients at baseline and after two weeks of treatment with selumetinib. FLT uptake in tumor was compared to CT scans at baseline and eight weeks to evaluate the utility of 18 F-FLT PET as an early predictor of response.…”
Section: Biomarkers Of Metabolic Effectmentioning
confidence: 99%
“…In two patients, changes in FLT uptake as early as after two weeks of treatment were consistent with CT results after eight weeks. 105 Magnetic resonance spectroscopy. Cancer cells are known to reprogram their metabolism to facilitate tumor growth and survival by alteration of signaling pathways, which lead to alterations in glucose, glutamine, and lipid metabolism.…”
Section: Biomarkers Of Metabolic Effectmentioning
confidence: 99%
“…Extracellular signal-regulated protein kinase (ERK)1/2 is a mitogen-activated protein kinase (MAPK) family protein with typical cascade signaling characteristics and serves an important role in signal transduction pathways and the function of transcription factors, including activator protein-1, proto-oncogene c-Fos (c-Fos) and ETS domain-containing protein Elk-1 (Elk1) (9). The majority of research has focused on its regulatory effect on cell growth and differentiation (1014); however, a number of previous studies demonstrated that ERK1/2 promotes cell senescence (1517). Based on these characteristics, numerous small molecule MAPK/ERK kinase (MEK) inhibitors were examined in early-phase clinical trials, including PD098059, U0126, CI-1040, PD0325901 and AZD6244 (18); however, none of them were approved by The Food and Drug Administration due to adverse side effects or other toxic reactions (18).…”
Section: Introductionmentioning
confidence: 99%